Structural Consequences of Kcna1 Gene Deletion and Transfer in the Mouse Hippocampus - Wenzel, H. Jürgen; Vacher, Helene; Clark, Eliana; Trimmer, James S.; Lee, Angela L.; Sapolsky, Robert M.; Tempel, Bruce L.; Schwartzkroin, Philip A. (Epilepsia (Copenhagen), 2007)
Summary Purpose: Mice lacking the Kv1.1 potassium channel α subunit encoded by the Kcna1 gene develop recurrent behavioral seizures early in life. We examined the neuropathological consequences of seizure activity in the Kv1.1−/− (knock‐out) mouse, and explored the effects of injecting a viral vector carrying the deleted Kcna1 gene into hippocampal neurons. Methods: Morphological techniques were used to assess neuropathological patterns in hippocampus of Kv1.1−/− animals. Immunohistochemical and biochemical techniques were used to monitor ion channel expression in Kv1.1−/− brain. Both wild‐type and knockout mice were injected (bilaterally into hippocampus) with an HSV1 amplicon vector that contained the rat Kcna1 subunit gene and/or the E. coli lacZ reporter gene. Vector‐injected mice were examined to determine the extent of neuronal infection. Results: Video/EEG monitoring confirmed interictal abnormalities and seizure occurrence in Kv1.1−/− mice. Neuropathological assessment suggested that hippocampal damage (silver stain) and reorganization (Timm stain) occurred only after animals had exhibited severe prolonged seizures (status epilepticus). Ablation of Kcna1 did not result in compensatory changes in expression levels of other related ion channel subunits. Vector injection resulted in infection primarily of granule cells in hippocampus, but the number of infected neurons was quite variable across subjects. Kcna1 immunocytochemistry showed “ectopic” Kv1.1 α channel subunit expression. Conclusions: Kcna1 deletion in mice results in a seizure disorder that resembles—electrographically and neuropathologically—the patterns seen in rodent models of temporal lobe epilepsy. HSV1 vector‐mediated gene transfer into hippocampus yielded variable neuronal infection.